The variability of the urban landscape in Italy - Vittorio Ruggiero; Luigi Scrofani; Claudio Novembre (European Regional Science Association (ERSA), 2010)
Since the early 90s of last century, the city is returned to the focus of European and national policies and new theories of urban development inspired by the theme of regeneration and the new centrality of the historical part of the city. In recent years interesting process of reconstruction and rehabilitation of historic areas have been, but also experimental steps towards new means of intervention of the city and new content that contributed to the review of practice of interventions in the territory based on two key themes of the functional organization and the satisfaction of an increasing housing needs. Many Italian cities have launched plans and proposals for urban regeneration of the old town, enriched by new instances related to the values and concrete social practices of participation and environmental sustainability. A raised dynamism linked to the redistribution of functions between the city centre, specialized in business skills, and an ever-expanding suburbs, which tends to create a diffuse urban systems. The theme of the re-qualification of the historic centre of Italian cities, therefore, is placed at the intersection of an urban policy seeks to address the continuing problems of quality of life and physical degradation of infrastructure and the need to revitalize the city and its ability attractiveness in terms of investment, functions, visitors and new residents. In particular, the frequent cases of property speculation, with the expulsion from the city centre for residents of restored areas, have made clear that the re-qualification can never be just based on building but have to be social to link virtuous pieces of fragmented communities. In this paper the authors, using statistical indicators too, have been analyzed not only the process of regeneration of the Italian cities but also the evolution of urban space to a model focused on quality and competitiveness. But to understand the attractiveness and competitiveness of the urban area was also fundamental the study of the image that reflects the city, because it leads many people to visit, shop and spend their free time there.
Keywords: 330